2020
DOI: 10.3389/fimmu.2020.00609
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota and Immunity Defines Plasmodium vivax Survival in Anopheles stephensi

Abstract: Blood-feeding enriched gut-microbiota boosts mosquitoes' anti-Plasmodium immunity.Here, we ask how Plasmodium vivax alters gut-microbiota, anti-Plasmodial immunity, and impacts tripartite Plasmodium-mosquito-microbiota interactions in the gut lumen. We used a metagenomics and RNAseq strategy to address these questions. In naïve mosquitoes, Elizabethkingia meningitis and Pseudomonas spp. are the dominant bacteria and blood-feeding leads to a heightened detection of Elizabethkingia, Pseudomonas and Serratia 16S … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 54 publications
2
47
0
Order By: Relevance
“…42 Our recent study suggests that P. vivax infection restricts gut-flora proliferation, which consequently facilitates Plasmodium development. 34 In this study, we observed that P. vivax infection not only caused a limited change in the expression of hemocyte FREP13 (Figure 6a) during the late phase but also caused significant downregulation in the midgut during the early phase of infection (Figure 6b). Together with these data, we hypothesize that hemocyte-encoded AsFREP13 may have a key role in the regulation of gut microbial population, which concomitantly affects P. vivax development.…”
Section: Hemocyte Asfrep13 Regulates Cross Tissue Gut-flora Proliferamentioning
confidence: 49%
See 4 more Smart Citations
“…42 Our recent study suggests that P. vivax infection restricts gut-flora proliferation, which consequently facilitates Plasmodium development. 34 In this study, we observed that P. vivax infection not only caused a limited change in the expression of hemocyte FREP13 (Figure 6a) during the late phase but also caused significant downregulation in the midgut during the early phase of infection (Figure 6b). Together with these data, we hypothesize that hemocyte-encoded AsFREP13 may have a key role in the regulation of gut microbial population, which concomitantly affects P. vivax development.…”
Section: Hemocyte Asfrep13 Regulates Cross Tissue Gut-flora Proliferamentioning
confidence: 49%
“…Surprisingly, we also noticed that AsFREP13 silencing causes a greater suppression of Elizabethkingia, a dominant gut endosymbiont, 34 and favors Pseudomonas proliferation after blood-feeding in mosquitoes. Taken together, these data strongly suggest that hemocyteencoded AsFREP13 may have a unique role in the regulation and maintenance of gut immunophysiological homeostasis.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations